Surgical techniques on periodontal plastic surgery and soft tissue regeneration: Consensus Report of Group 3 of the 10th European Workshop on Periodontology. (April 2014) - Sanz, Mariano; Simion, Massimo; ,
Abstract: Background: The scope was to review the three main clinical indications in periodontal plastic surgical procedures. Aims: To review the fundamental principles in periodontal plastic surgery, the main surgical designs in flap surgery applied to the treatment of recessions, peri‐implant soft tissue deficiencies and soft tissue ridge augmentation, as well as the surgical principles of using autologous connective tissue grafts and soft tissue substitutes. Fundamental Principles in Plastic Surgery: In the pre‐operative phase, the key elements are the control of prognostic factors affecting the patient, namely oral hygiene, tobacco smoking cessation and systemic disease control. In the operative phase, the principles of flap design, mobilization, advancement, adaptation and stabilization. In the post‐operative phase infection control, including effective oral hygiene measures, antiseptic treatment and other medications. Critical Elements in Flap Design and Surgical Execution: In single recession defects, the most widely used flap technique is the coronally advanced flap and in specific clinical situations the laterally positioned flap. In multiple recession defects, the number of defects and their location and depth guide the surgical design, being one design with and the other without vertical releasing incisions. When flaps are used in combination with grafts the tunnel flap is also used extensively. Critical Elements in the Use of Soft Tissue Replacement Grafts: The key elements are the donor site selection and harvesting technique, its tissue integration and volume stability. Clinical Recommendations: Given the current evidence, various clinical recommendations on the use of flaps and grafts are provided.